2019
DOI: 10.3389/fimmu.2019.00385
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri Reduces the Severity of Experimental Autoimmune Encephalomyelitis in Mice by Modulating Gut Microbiota

Abstract: The gut microbiome plays an important role in immune function and has been implicated in multiple sclerosis (MS). However, how and if the modulation of microbiota can prevent or treat MS remain largely unknown. In this study, we showed that probiotic Lactobacillus reuteri DSM 17938 (L. reuteri) ameliorated the development of murine experimental autoimmune encephalomyelitis (EAE), a widely used animal model of MS, a model which is primarily mediated by TH17 and TH1 cells. We discovered that L. reuteri treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
105
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 66 publications
(54 reference statements)
10
105
0
2
Order By: Relevance
“…Lactobacillus dysbiosis was also shown to be present in an animal model of depression and therapeutic supplementation with L. reuteri was sufficient to improve depressive-like symptoms 18 . Here, we have demonstrated that L. reuteri supplementation was beneficial in mice undergoing EAE, further confirming a recent study 19 . Our community analysis suggests that Lactobacillus may be a keystone species of the gut flora, as its decrease correlates with microbial community reorganization.…”
Section: Discussionsupporting
confidence: 91%
“…Lactobacillus dysbiosis was also shown to be present in an animal model of depression and therapeutic supplementation with L. reuteri was sufficient to improve depressive-like symptoms 18 . Here, we have demonstrated that L. reuteri supplementation was beneficial in mice undergoing EAE, further confirming a recent study 19 . Our community analysis suggests that Lactobacillus may be a keystone species of the gut flora, as its decrease correlates with microbial community reorganization.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, we show that oral treatment with Lactibiane iki improves the clinical outcome of EAE mice in a dose-dependent manner as a therapeutic approach. The clinical improvement was related to decreased CNS demyelination and inflammation, as corroborated by many previous studies of probiotic treatment [7][8][9][10][11][12][13]. Lactibiane iki treatment also decreases the expression of the Th17-defining transcription factor Rorγt in the spinal cord, revealing a reduction in this pro-inflammatory cell population previously connected to both EAE [45] and MS [46] pathogenesis in the CNS.…”
Section: Discussionsupporting
confidence: 81%
“…However, experimental data support the idea that some bacterial strains, far from being harmful, have a beneficial impact on the outcome of EAE. Thus, the promotion of beneficial microorganisms via probiotics is being developed as an important therapeutic strategy involving the gut microbiota in EAE [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Erysipelotrichaceae abundance has been negatively correlated with body fat weight, the colonic butyrate concentration and intestinal health [74]. Rikenellaceae abundance has been positively correlated with clinical disease severity [75], and a reduced proportion of Rikenellaceae is considered to be a signature of a healthy gut. Recent evidence suggested that butyrate reduces the incidence and severity of NE, thus preventing ascending infections when added to feed [76].…”
Section: Discussionmentioning
confidence: 99%